Hedging from the Perspective of Maqasid Shariah - Hernawaty; Nurhayati; Harahap, Isnaini (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
The growing volatility of global exchange rates presents significant risks for emerging economies, particularly those heavily reliant on foreign-denominated debt, such as Indonesia. Conventional hedging instruments, while mitigating currency risk, often conflict with Islamic financial principles due to elements of riba (interest), gharar (uncertainty), and maisir (speculation). This study proposes a Shariah-compliant hedging framework grounded in Maqasid al-Shariah to offer an ethical and sustainable alternative to conventional risk management tools. Through simulation modeling, the study explores the potential of Islamic forward contracts and cross-currency swaps in strengthening external debt resilience while adhering to Islamic principles. The research anticipates that Maqasid al-Shariah will significantly drive the adoption of Islamic hedging mechanisms, enhancing financial stability in both local and international contexts. Moreover, Shariah-compliant instruments are expected to mediate the relationship between ethical objectives and exchange rate stability, offering dual benefits of compliance and economic resilience. By addressing the intersection of Islamic finance, global economic risk, and sustainable development, this study provides theoretical contributions and practical policy recommendations. The findings aim to support regulators, financial institutions, and international stakeholders in promoting Shariah-based financial innovation as a critical component of global financial stability in the face of ongoing economic uncertainties.